2021
DOI: 10.1097/ju.0000000000001984.18
|View full text |Cite
|
Sign up to set email alerts
|

Mp11-18 the Concordance Between Conventional Computed Tomography and Nuclear Medicine Bone Scintigraphy in the Identification of Prostate Cancer Metastases to Bone

Abstract: INTRODUCTION AND OBJECTIVE: A previously reported Prostatype algorithm (P-score) incorporating a three-gene signature (IGFBP3, F3, VGLL3) with clinical parameters (Gleason score, PSA and T-stage) was developed and validated in 596 historical patients selected from a population-based cohort. This study aims to retrospectively validate Prostatype algorithms capability to predict the risk of metastasis and prostate cancer (PCa) specific mortality in new diagnosed PCa patients.METHODS: All 716 patients included we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Prostate cancer is more and more diagnosed in Benin since the introduction of TRUS-guided prostate biopsy in 2013 [2] The advent of choline and PSMA positron emission tomography has revealed that the whole-body scintigraphy can miss up to 24% bone metastatic prostate cancer patients [12]. The computed tomography is available in our country, but it does not perform better than bone scintigraphy [13]. The whole-body magnetic resonance imaging if it is available, may be helpful in non-claustrophobic patients [14] [15].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is more and more diagnosed in Benin since the introduction of TRUS-guided prostate biopsy in 2013 [2] The advent of choline and PSMA positron emission tomography has revealed that the whole-body scintigraphy can miss up to 24% bone metastatic prostate cancer patients [12]. The computed tomography is available in our country, but it does not perform better than bone scintigraphy [13]. The whole-body magnetic resonance imaging if it is available, may be helpful in non-claustrophobic patients [14] [15].…”
Section: Discussionmentioning
confidence: 99%